Selection of head and neck cancer patients for adaptive radiotherapy to decrease xerostomia. Issue 1 (July 2016) - Brouwer, Charlotte L.; Steenbakkers, Roel J.H.M.; van der Schaaf, Arjen; Sopacua, Chantal T.C.; van Dijk, Lisanne V.; Kierkels, Roel G.J.; Bijl, Hendrik P.; Burgerhof, Johannes G.M.; Langendijk, Johannes A.; Sijtsema, Nanna M.
Abstract: Background and purpose: The aim of this study was to develop and validate a method to select head and neck cancer patients for adaptive radiotherapy (ART) pre-treatment. Potential pre-treatment selection criteria presented in recent literature were included in the analysis. Materials and methods: Deviations from the planned parotid gland mean dose (PG ΔDmean) were estimated for 113 head and neck cancer patients by re-calculating plans on repeat CT scans. Uni- and multivariable linear regression analyses were performed to select pre-treatment parameters, and ROC curve analysis was used to determine cut off values, for selecting patients with a PG dose deviation larger than 3 Gy. The patient selection method was validated in a second patient cohort of 43 patients. Results: After multivariable analysis, the planned PG Dmean remained the only significant parameter for PG ΔDmean. A sensitivity of 91% and 80% could be obtained using a threshold of PG Dmean of 22.2 Gy, for the development and validation cohorts, respectively. This would spare 38% (development cohort) and 24% (validation cohort) of patients from the labour-intensive ART procedure. Conclusions: The presented method to select patients for ART pre-treatment reduces the labour of ART, contributing to a more effective allocation of the department resources.